Model-free based adaptive nonsingular fast terminal sliding mode control with time-delay estimation for a 12 DOF multi-functional lower limb exoskeleton. (May 2018) - Han, Shuaishuai; Wang, Haoping; Tian, Yang
Highlights: This research proposes a model free MFANFTSMC strategy for the developed 12 DOF multi-functional lower limb exoskeleton. The 12 DOF exoskeleton is developed including adjustable mechanical design, virtual prototype realization and inverse kinematic solution. A model independent intelligent PI (iPI) controller is designed based on the unltra-local and time delay estimation (TDE) technique. To compensate the estimation errors in TDE, the adaptive NFTSMC is combined to the proposed iPI controller. Co-simulation is conducted to illustrate the effectiveness of MFANFTSMC, compared to existing model free control. Abstract: The design of a 12 DOF lower limb multi-functional exoskeleton is realized in SolidWorks with the analysis of kinematics. For controller design, this paper presents the model-free based adaptive nonsingular fast terminal sliding mode control which comprises three parts: the intelligent PI controller, time-delay estimation, and adaptive sliding mode compensator. The proposed control strategy drives tracking errors to a nonsingular fast terminal sliding surface and realizes fast convergence in finite time. The designed adaptive law approximates the upper bound of estimation error in time-delay estimation and thus it reduces the fundamental chattering on the switching manifold. The stability of controller is verified by using Lyapunov theory. To validate the proposed method, the virtual prototype is transferred to MATLAB/SimMechanics as a platform for co-simulation. The proposed method shows improved tracking performance compared with the existing model free controller in co-simulations.